2017
DOI: 10.1016/j.jana.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

“Against Medical Advice” Discharges Among HIV-Infected Patients: Health and Health Services Outcomes

Abstract: Nurses are often first to identify and manage a patient leaving against medical advice (AMA), and so they are critical contributors to the development of strategies to address this problem. We studied AMA discharge in order to help develop useful interventions. We performed a cross-sectional analysis of 55,938 discharges from a single urban hospital for the years 2002-2003 and 2012-2013. AMA discharge rates were higher for HIV-infected patients than for patients with alcohol-related disorders or sickle cell an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Indeed, discharge against medical advice had already been associated with increased risk of 30-day readmission in the general population 31 and among those with HIV 13,21,32 . Interestingly, compared to HIV-uninfected patients, HIV infected patients were shown to have a higher risk of leaving the hospital against medical advice 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, discharge against medical advice had already been associated with increased risk of 30-day readmission in the general population 31 and among those with HIV 13,21,32 . Interestingly, compared to HIV-uninfected patients, HIV infected patients were shown to have a higher risk of leaving the hospital against medical advice 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, discharge against medical advice had already been associated with increased risk of 30-day readmission in the general population 31 and among those with HIV 13,21,32 . Interestingly, compared to HIV-uninfected patients, HIV infected patients were shown to have a higher risk of leaving the hospital against medical advice 32 . Specifically, among HIV infected patients, leaving hospital against medical advice led to a 5-fold increased odds of 30-day readmission for a related diagnosis and was associated with longer readmission LOS (compared to those who had been formally discharged) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-day readmission rates following patient-directed discharge during infection treatment are consistently elevated across studies [12,[17][18][19], indicating the potential for ineffective treatment. Our findings of high 30-day and one-year readmission rates among persons who use drugs with patient-directed discharge are consistent with existing data.…”
Section: Discussionmentioning
confidence: 99%
“…The following characteristics that have been previously associated with readmission were accounted for as potential confounders in this analysis: patient’s age at admission (per 10 year increase); sex (female vs male); calendar year (per 10-year increase); history of injection drug use (yes vs unknown vs no [reference]); Charlson comorbidity index (per unit increase); patient CD4 cell count measured within 12 months of admission date (100 cells/mL); viral load (log 10 increase); and discharge against medical advice (yes vs no). 13,18,30,4446…”
Section: Methodsmentioning
confidence: 99%
“…In the context of HIV, the continuum of care relies on engaging and retaining PLWH in care. It is known that patients who leave hospital against medical advice (i.e., are not retained in care) are more likely to be readmitted with a worsened condition and have higher rates of mortality 18 To prevent this, evidence has suggested that engaging with the primary care system and being attached to a healthcare provider in the community may reduce hospital utilization among patients. 19,20 Indeed, a growing number of studies suggest that suboptimal care during hospitalization and after discharge, such as wrong or missed diagnosis or premature discharge, is negatively associated with unplanned 30-day readmission.…”
Section: Introductionmentioning
confidence: 99%